2016
DOI: 10.1016/j.jfda.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ERK1/2 and hypoxia pathways by four Phyllanthus species inhibits metastasis of human breast cancer cells

Abstract: Chemotherapies remain far from ideal due to drug resistance; therefore, novel chemotherapeutic agents with higher effectiveness are crucial. The extracts of four Phyllanthus species, namely Phyllanthus niruri, Phyllanthus urinaria, Phyllanthus watsonii, and Phyllanthus amarus, were shown to induce apoptosis and inhibit metastasis of breast carcinoma cells (MCF-7). The main objective of this study was to determine the pathways utilized by these four Phyllanthus species to exert anti-metastatic activities. A can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…ROS activate diverse signaling pathways, including the p42/p44 MAPK, p38 MAPK, and PI3K/Akt pathways (37) and have important roles, such as cell cycle, survival, and cell death. The MAPK and Wnt pathways are involved in the regulation of cancer cell proliferation, differentiation, and death (38,39). Here we evaluated the genes and signaling pathways that were altered in primary tumor tissues in a xenograft mouse model on an HCD with or without FBX cotreatment.…”
Section: ×2mentioning
confidence: 99%
“…ROS activate diverse signaling pathways, including the p42/p44 MAPK, p38 MAPK, and PI3K/Akt pathways (37) and have important roles, such as cell cycle, survival, and cell death. The MAPK and Wnt pathways are involved in the regulation of cancer cell proliferation, differentiation, and death (38,39). Here we evaluated the genes and signaling pathways that were altered in primary tumor tissues in a xenograft mouse model on an HCD with or without FBX cotreatment.…”
Section: ×2mentioning
confidence: 99%
“…Studies have shown that MAPKs pathway is essential in the progression of cancer, which do control cell growth, migration, proliferation, and differentiation . MAPKs (ERK1/2, JNK and p38) are protein‐serine/threonine kinases, which could be activated through phosphorylation, beginning with the induction of MAPK kinase kinases (MAP3Ks) to adjust cell fates …”
Section: Resultsmentioning
confidence: 99%
“…MAPKs pathway is essential in cancer progression, which could control cell differentiation, proliferation, and migration . Studies have shown that the activation of MAPKs pathways is involved to the therapeutic resistance for various cancers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations